Development of a Methodology for Creating Educational Projects on Educational Robotics Based on STEM Disciplines - Sanjar Kanatuly Gauyezkhan (World Scientific Reports, 2025)
This article explores the theoretical and practical foundations for creating educational projects in the field of educational robotics based on STEM disciplines. It highlights modern platforms such as LEGO WeDo 2.0, SPIKE, and Arduino, which integrate engineering thinking, programming, and scientific knowledge. The proposed methodology aims to develop students’ research and creative competencies.